A cross sectional study on antipsychotic induced amenorrhoea in women attending a tertiary care centre in South India - Savarimuthu, Monisha Kanya; Bhaskar, Srisudha; Alexander, Anu Mary; Kurian, Suja (International Journal of Research in Medical Sciences, 2019)
Background: Absence of menstrual period in a woman of reproductive age group could be physiological or pathological. Ascertaining the cause for this is a common clinical scenario faced by physicians. It is also a common clinical problem in women who are on treatment with antipsychotic medication. This cross-sectional study aimed to assess the occurrence of antipsychotic induced amenorrhoea among women aged 18-45 years, attending outpatient services of a tertiary care setting, the factors associated and to assess the effective strategies of treatment. Methods: Retrospective chart review of clinical details of women in the reproductive age group who fulfilled the inclusion criteria was carried out. They were divided into two groups: Group A included 84 women with antipsychotic induced amenorrhea and Group B included 94 women on antipsychotics and had normal menstrual cycles. Various factors and strategies which worsened or alleviated the symptoms were noted. Results: Women who were less than 35 years of age, on antipsychotic treatment for more than two years duration (52;83.9%) and those who were on treatment with Risperidone (69;73.4%) were identified as having the risk of developing antipsychotic induced amenorrhoea. The strategy of switch of medication to prolactin sparing antipsychotic was more effective in regularising the menstrual cycles (43;87.8%). Conclusions: In women presenting with amenorrhoea, a possible medication induced aetiology need to be considered, especially use of antipsychotics. Further understanding of the complexities of this relationship may help to guide the assessment and proper treatment of women with antipsychotic related amenorrhoea.